Boundary Problem Solution Algorithm for the Task of Controlled Spacecraft Motion in Irregular Gravitational Field of an Asteroid. (2017) - Shornikov, Andrey; Starinova, Olga
Abstract: The problem of controlled spacecraft motion in vicinity of asteroids is an important flight dynamics task. Solution of the problem consists of gravitational field simulations and control trajectory scheme defininition. We propose to use the model of single gravity points for motion simulation of a spacecraft in an irregular gravitational field of the Eros 433 asteroid. The equations of spacecraft motion are the corresponding equations of the n-body problem. The motion trajectory can be split into a number of from-point-to-point motion parts. Each part can be considered as a two-point Boundary task. The Authors developed a concept of Boundary problem solution based on the Pontryagin's principle and modified Newton's step-by-step approximation method. The Authors developed a special software for the Boundary problem solutions. A boundary task of the controlled spacecraft's transfer between circular orbits from 200 km to 100 km is presented in the paper.